An Investigation of the Extrapolative Determinants of Short-Run Earnings Expectations - McEnally, Richard W. (Journal of Financial and Quantitative Analysis, 1971)
The pivotal role of earnings expectations in equity valuation and therefore in certain areas of business finance is widely recognized, yet there is little theoretical or empirical evidence as to the manner in which investors and other groups actually formulate their estimates of future earnings. The resulting necessity to utilize proxy or indirect measures of expected earnings specified largely according to the predispositions of the investigator has led to numerous difficulties in the testing of cost of capital propositions and models of equity valuation.1 This study is intended to supply a preliminary response to the question of how earnings expectations are determined by appraising the extrapolative component of a limited sample of short-term estimates of earnings per common share. More specifically, the issues are the extent to which the earnings estimates (1) are extrapolative in nature and (2) may be approximated by familiar, naive, extrapolative techniques. In this context, “extrapolative” simply means determined by application of a specified weighting scheme to prior observations in the time series.